From governance to growth: comparative insights on institutional reforms in China and Latin America - Valdiglesias, Jhon (Frontiers in Political Science, 2025)
IntroductionThis study examines the effects of China’s rule-of-law reforms and anti-corruption measures under Xi Jinping on economic performance, using China as a benchmark to compare with seven Latin American countries. It aims to explain how different institutional trajectories shape governance quality and long-term growth.MethodsThe analysis draws on two decades of panel data and employs fixed and random effects models with interaction terms to investigate how improvements in corruption control and the rule of law influence economic performance. China is systematically compared with selected Latin American countries to highlight divergent institutional dynamics.ResultsThe results show that China’s state-led institutional reforms have strengthened bureaucratic efficiency, policy coordination, and investment conditions, fostering sustained economic expansion. In contrast, Latin America’s fragmented institutions, weak enforcement of legal frameworks, and persistent corruption limit the effectiveness of governance reforms, constraining economic growth.DiscussionBy systematically comparing China and Latin America, this study contributes to comparative political economy by demonstrating how targeted, state-driven institutional reforms can shape governance quality and long-term developmental trajectories.